Multiple-alphabet amino acid sequence comparisons of the immunoglobulin kappa-chain constant domain. - Karlin, S (1985)
We compare the amino acid sequences of the constant domains of the immunoglobulin kappa chain of human, mouse, and rabbit by using four classification schemes ("alphabets") of the 20 amino acids based on their chemical, functional, charge, and structural properties. The comparison reveals three regions of pronounced similarity across the three species, independent of allotype. Two of these regions (residues 65-73 and 99-103) entail a high degree of identity at the DNA level and are distinguished from the rest of the constant domain in codon usage and in the dinucleotide sequence at abutting sites of adjacent codons. Residues 22-29 are highly conserved among the three species in the chemical and functional alphabets but do not show any three-sequence significant amino acid block identities. These results are discussed in terms of transcript processing, effector functions, and structural interactions within the constant domain and with the heavy chain.